The Effectiveness of Class Motivators in Increasing Compliance with the Consumption of Blood Supplement Tablets in Junior High School Girls - Risnawati, Risnawati; Maidar, Maidar; Zahara, Meutia (Indonesian Journal of Global Health Research, 2024)
Blood supplementation tablets through the nutritional action program have been implemented, but coverage is still 74.29% of the 100% target. Peer support is thought to be an important factor influencing adherence to Fe tablet consumption. This study aims to determine the effectiveness of class motivators in increasing compliance with the consumption of blood supplement tablets among young women in Pidie Regency. This research is a quantitative research designas if the experiment were not equivalent use pretest and posttest control group design. Implemented in Pidie Regency from October 2023 to January 2024. The population consists of all female students at MTsN 5 Pidie (567) as the intervention group and SMP N 2 Delima (262) as the control group. The total sample was 628 female students who met the inclusion criteria, with 368 in the intervention group and 260 in the control group. Data collection was carried out through questionnaires, and the formation of class motivators in the intervention group. Data analysis used Mann Whitney and Wilcoxon test statistics using the Stata 14 program. The results showed that there were differences in changes in adherence to consuming blood supplement tablets, knowledge, HB levels, side effects of tablets, consumption of enhancer foods, consumption of inhibitor foods and belief in myths between the intervention groups. and the control group in increasing the consumption of blood supplement tablets, and there was no difference in changes in attitudes (p=0.308) between the intervention group and the control group in increasing the consumption of blood supplement tablets. Compliance with consuming blood supplement tablets among female students has increased in the group given class motivator intervention, which significantly increased compliance with consuming blood supplement tablets, knowledge, HB levels, side effects of tablets, consumption of enhancer foods, consumption of inhibitor foods and belief in myths. However, there was no difference in the attitudes of the intervention and control groups, this was because the respondents' attitudes were good from the start.